P-033 When to stop: the marginal utility of additional thrombectomy passes. (22nd July 2018) - Raymond, S; Koch, M; Rabinov, J; Leslie-Mazwi, T; Stapleton, C; Patel, A
Abstract : Introduction/purpose: Endovascular mechanical thrombectomy is the most effective treatment for patients presenting with acute large vessel occlusion. However, recanalization is sometimes not achieved even after multiple passes of the thrombectomy device. Repeated attempts at clot retrieval come at a cost of increased procedure time and risk of complications. Clear criteria for when to halt attempting recanalization do not currently exist. We address this question by estimating the probability of recanalization after each pass and compare this with the decreased outcomes associated with multiple passes. Materials and methods: We studied a retrospective group of patients treated with mechanical thrombectomy for large vessel occlusion at a single center from 2012–2017. For each patient, the TICI reperfusion score after each pass (including aspiration, stentriever, or wire manipulation) was estimated by reviewing the angiography and associated procedure report. Adequate reperfusion was defined as TICI 2b/3. Demographics were obtained from the electronic medical record and included age, gender, vascular risk factors, presenting NIHSS and mRS, procedure time, discharge mRS, and periprocedural complications. Statistics were computed using the open source, R statistics platform. Results: Reperfusion with TICI 2b/3 was achieved in 146 of 198 patients (74%) after on average 1.8 thrombectomy passes (median 1, IQR 1–3). Most patients underwent stentriever thrombectomy or some combination of aspiration and stentriever. The probability of achieving TICI 2b/3 peaked on the third pass. Although many patients achieved TICI 2b/3 after three or more passes, the probability of achieving TICI 2b/3 decreased precipitously after the third pass. No patients achieved TICI 2b or 3 on the fifth or sixth pass. Patients were sub-stratified by number of passes (1–3 or >3). The group with greater than 3 passes was less likely to achieve TICI 2b or 3 (7/18 (39%) compared with 139/172 (82%), p=0.003) and less likely to achieve good functional outcome, mRS 0–2 (3/18 (17%) compared with 78/164 (48%), p=0.01). The number of passes was weakly correlated with the procedure duration (R 2 0.4). Conclusion: With modern aspiration catheters and stentrievers, target reperfusion is usually achieved within 3 passes. Patients who require greater than 3 passes are less likely to achieve TICI 2b/3 reperfusion and more likely to have poor outcomes. Because the probability of recanalization markedly decreases after 3 passes, and is lost after 5 passes, the diminishing benefit of repeated recanalization attempts must be weighed against the additive risks. Disclosures: S. Raymond: None. M. Koch: None. J. Rabinov: None. T. Leslie-Mazwi: None. C. Stapleton: None. A. Patel: 2; C; Medtronic, Penumbra.